Corporate Governance Reforms: Redefined Expectations of Audit Committee Responsibilities and Effectiveness - Vera-Muñoz, Sandra C. (Journal of business ethics, 2005)
Comprehensive regulatory changes brought on by recent corporate governance reforms have broadly redefined and re-emphasized the roles and responsibilities of all the participants in a public company’s financial reporting process. Most notably, these reforms have intensified scrutiny of corporate audit committees, whose role as protectors of investors’ interests now attracts substantially higher visibility and expectations. As a result, audit committees face the formidable challenge of effectively overseeing the company’s financial reporting process in a dramatically changed – and highly charged – corporate governance environment. This paper discusses the new expectations of audit committee responsibilities and effectiveness in the wake of corporate governance reforms, key challenges, “whistleblower” provisions and shortcomings, and provides some directions for future research.